A Typology of Mathematics Teachers' Beliefs About Teaching and Learning Mathematics and Instructional Practices - Barkatsas, Anastasios; Malone, John (Mathematics Education Research Group of Australasia, 2005)
The primary purposes of the study reported here were to investigate Greek mathematics teachers’ beliefs regarding the nature of mathematics and mathematics teaching and learning, and to explore the various links between these beliefs and instructional practice. Two orientations that are characteristic of secondary mathematics teachers’ beliefs were identified: A contemporary — constructivist orientation, and a traditional — transmission — information processing orientation. A case study of a veteran teacher demonstrated that classrooms can be complex sites of political, historical, social and cultural influences, and that the teacher’s beliefs about mathematics learning and teaching were less traditional than her actual teaching practice.